Productivity spillovers from foreign direct investment in Kenya's manufacturing sector - Wycliff Mariga Ombuki; Bethuel Kinyanjui Kinuthia; Daniel Okado Abala (Cogent Economics & Finance)
This paper seeks to determine the transmission channels of foreign direct investment-induced productivity spillovers in the manufacturing sector in Kenya and investigate whether or not firm-level heterogeneity responds to the transmission channels. We analyze panel data obtained from the World Bank database for the period 2007–2018. Employing fixed effects and Two-Step System GMM, we empirically demonstrate the relevance and significance of distinguishing four spillover transmission channels–demonstration effects, labour mobility, competition effects, and backward linkages. Overall, the results show negative productivity spillovers through the backward linkage channel, whereas spillovers through labour mobility, demonstration, and competition effects channels show unstable patterns across various specifications. The results also show that productivity spillovers depend on the technology gap between domestic and foreign firms while firm size had no significant impact. The findings suggest the need for firms to enhance their technology levels, invest in value addition and increase their absorption capacities in order to realize spillover benefits from foreign direct investment.